Strong Interface Construction of Carbon Fiber–reinforced PEEK Composites: An Efficient Method for Modifying Carbon Fiber with Crystalline PEEK - Yang, Yanchao; Wang, Tianjiao; Wang, Shengdao; Cong, Xin; Zhang, Shuling; Zhang, Mei; Luan, Jiashuang; Wang, Guibin (Macromolecular rapid communications., 2020)
In order to improve the poor solvent resistance and poor temperature resistance caused by traditional sizing agents, crystalline poly(ether ether ketone) (PEEK) is introduced to the interfacial phases of carbon fiber (CF) reinforced PEEK composites by a soluble precursor named PEEK‐1,3‐dioxolane. By changing the soluble precursor molecular weight and concentration in the sizing solution, the content of PEEK coated on the CF fiber surface can be controlled and the different interfacial properties of the PEEK composites can be obtained. The results shows that, with this method, crystalline PEEK can be completely coated on the CF surface, and the interfacial shear strength of the PEEK composites increases from 43.42 to 83.13 MPa. Due to none of any soluble compounds in the PEEK composites, the interfacial layer is well preserved under organic solvents and hygrothermal conditions, and the interfacial shear strength (IFSS) of the PEEK composites maintained above 85.4% and 90.44%, respectively. Scanning electron microscope clarifies that the mechanism of interface enhancement comes from a better wetting of crystalline PEEK on the fiber surface. Additionally, the sizing system of this investagation has the potential commercial value because of no toxic reagent (such as 2,4,5‐trichloro‐1‐hydroxy‐benzene or concentrated sulfuric acid) is required during sizing. Carbon fiber is modified by crystalline poly(ether ether ketone) (PEEK) through a soluble precursor. The modified carbon fiber–reinforced PEEK composite has an interfacial shear strength (IFSS) of 78 MPa, which remains above 85% even after soaking in 1‐methyl‐2‐pyrrolidinone for 72 h. At the same time, the sizing process can be simply implemented through general‐purpose factory equipment.